Why is Economic Geography not an Evolutionary Science? - Ron Boschma; Koen Frenken (European Regional Science Association (ERSA), 2004)
This paper explains the main commonalities and differences between neoclassical, institutional and evolutionary approaches that have been influential in economic geography during the last couple of decades. For all three approaches, we argue that they are in agreement in some respects and in conflict in other respects. While explaining to what extent and in what ways the Evolutionary Economic Geography approach differs from the Neoclassical (or `new') Economic Geography and the Institutional Economic Geography, we can specify the value-added of economic geography as an evolutionary science. Finally, we briefly outline a research agenda of the Evolutionary Economic Geography we like to explore.
Keywords: 330